KEPUTUSAN PEMBELIAN DITINJAU DARI KUALITAS PRODUK, VARIAN PRODUK DAN PROMOSI KOSMETIK PINKFLASH PADA KOMUNITAS COSPLAYER - Salsabilasetya Kusuma; Ida Aryati Diyah PW; Eny Kustiyah; Anna Probowati (JURNAL ILMIAH EDUNOMIKA, 2026)
This research aims to analyze the influence of product quality, product variants and promotions on purchasing decisions for Pinkflash cosmetics in the cosplayer community in Surakarta City. This research is motivated by the increasing consumption of cosmetic products in creative communities who have specific needs for product diversity and digital-based marketing strategies. The research method used is a quantitative approach with a survey design. The research sample consisted of 120 respondents who were members of the cosplayer community in Surakarta and had purchased Pinkflash cosmetics, who were selected using a purposive sampling technique. Data collection was carried out through a questionnaire with a Likert scale, then analyzed using multiple linear regression with the help of SPSS software. The results of the analysis show that product quality does not have a significant effect on purchasing decisions for Pinkflash cosmetics. This indicates that product quality is perceived as a basic factor that is inherent in cosmetic products, so it is not a main consideration in making purchasing decisions. On the other hand, product variants were proven to have a positive and significant influence on purchasing decisions, which shows that diversity in product types and colors is an important factor for the cosplayer community in adjusting character makeup needs. Apart from that, promotions also have a positive and significant influence on purchasing decisions, especially through digital promotions and social media which are relevant to the characteristics of young consumers. Thus, it can be concluded that the decision to purchase Pinkflash cosmetics in the cosplayer community in Surakarta is significantly influenced by product variants and promotions, while product quality does not have a significant influence. Keywords : purchasing decisions, product quality, product variants, promotions, cosmetics, cosplayers.